POTENSI WISATA KULINER SEBAGAI OBJEK WISATA DI KOTA BANDUNG - Superwiratni, Superwiratni; Karnita, Ita; Marini, Sri (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2024)
The development of culinary tourism in the city of Bandung has increased significantly. This is evidenced by the city of Bandung being named one of the cities with the best traditional food in Asia by the Taste Atlas Awards 2021. The diversity of Traditional Foods in the city of Bandung as well as abundant, diverse and unique raw materials provides a huge opportunity for the sale of culinary tourism in the city of Bandung because the potential for culinary tourism is supported by the attractiveness of culinary tourism in the city of Bandung. This research focuses more on the potential of traditional food, tourist attraction and culinary tourism. These things are the reasons this research must be done. The results showed that traditional food is a potential for the development of culinary tourism in Bandung City so that traditional food has a role in developing culinary tourism, especially in Bandung City.This research uses a qualitative approach. The informants are traditional food producers and sellers in the Bandung City area. The research location is in all areas of Bandung City. Data collection was carried out using observation, interview, and documentation study techniques